Strategi Gerakan Literasi di Sekolah Dasar Melalui Program Membaca Menyenangkan - Weda Buartami, Luh; Sukerni, Ni Kadek; Sari, Ni Made Ayu Liyoga; Sari, Made Eka; Maharani, Ni Komang Widya Dwi; Werang, Basillius Redan (PrimEarly : Jurnal Kajian Pendidikan Dasar dan Anak Usia Dini, 2024)
This Study was promted by concerns about the decline in reading interest among primary school students, which could potentially affect their literacy skills. This study aims to explore the impact of the School Literacy Movement (GLS) on the increase in reading interest of elementary school students and to evaluate the effectiveness of GLS as a solution in stimulating students' interest in reading. The research method used is a descriptive qualitative approach through direct observation, in-depth interviews with teachers and students. There was an overall increase in reading interest among elementary school students after they were actively involved in school literacy movement activities. The results of this study highlight the importance of a contextual and experiential approach in improving literacy, as well as the crucial role of the researcher's deep understanding of the research subject in generating meaningful insights.